2017
DOI: 10.1007/s12088-017-0686-9
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Production by a Novel Isolate of Microbacterium paraoxydans

Abstract: This study reports extraction and characterization of carotenoid pigments from , a non-photosynthetic bacterium, cultivated in Luria-Bertani (LB) medium. The isolate was identified to be moderately halo- and osmo-tolerant capable of withstanding high (~ 6%) salt and sugar (30% w/v sucrose, 20% w/v glucose) concentrations after a brief period of adaptation. The pigments were characterized using a combination of UV-Vis spectral analysis with the λ at 407, 436 and 466 nm and ESI-MS with an value at 536.44. The ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
7
1
3
Order By: Relevance
“…In addition to the previously mentioned authors, Ojha et al . 28 also detected neurosporene in the Microbacterium genus 28 . However, with the combined information of the UV-Visible spectra mentioned above and the results of APCI-MS, to our knowledge, it was the first time that the extracted sample was compared and matched to a purified neurosporene standard.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to the previously mentioned authors, Ojha et al . 28 also detected neurosporene in the Microbacterium genus 28 . However, with the combined information of the UV-Visible spectra mentioned above and the results of APCI-MS, to our knowledge, it was the first time that the extracted sample was compared and matched to a purified neurosporene standard.…”
Section: Resultsmentioning
confidence: 92%
“…Carotenoid pigments from Microbacterium paraoxydans were isolated and characterized by Ojha et al . 28 , and the finding of a neurosporene structure was also proposed.…”
Section: Resultsmentioning
confidence: 96%
“…Although it is reported that Microbacterium spp. can produce that those pigments (Ojha et al, 2018) among our isolates, none of them showed pigments in the culture conditions.…”
Section: Tablementioning
confidence: 67%
“…In the literature, among the carotenoids found in T. magnatum red patches, Bixin, b-carotene and cis-1-glycosyl-apo-8 0 -lycopene have been associated with Microbacterium spp. (Ojha et al, 2018). This species appears to be the most probable candidate for production, at least in part, of carotenoids in the truffle.…”
Section: Resultsmentioning
confidence: 91%
“… 76 Pigment production can be modulated by changing the carbon and nitrogen sources and salt concentrations in the growth medium. 77 In the future, we would like to test different carbon and nitrogen sources and salt concentrations to see if we can formulate a growth medium that will enhance decaprenoxanthin production in the stationary phase.…”
Section: Discussionmentioning
confidence: 99%